Antibody Generation and Immunogenicity Analysis of EBV gp42 N-Terminal Region - Junping Hong; Dongmei Wei; Qian Wu; Ling Zhong; Kaiyun Chen; Yang Huang; Wanlin Zhang; Junyu Chen; Ningshao Xia; Xiao Zhang; Yixin Chen (Viruses, 2021)
Epstein–Barr virus (EBV) is the first reported oncogenic virus and infects more than 90% of adults worldwide. EBV can establish a latent infection in B lymphocytes which is essential for persistence and transmission. Glycoprotein gp42 is an indispensable member of the triggering complex for EBV entry into a B cell. The N-terminal region of gp42 plays a key role in binding to gH/gL and triggering subsequent membrane fusion. However, no antibody has been reported to recognize this region and the immunogenicity of gp42 N-domain remains unknown. In the present study, we have generated a panel of nine mAbs against the gp42 N-terminal region (six mAbs to gp42-44-61aa and three mAbs to gp42-67-81aa). These mAbs show excellent binding activity and recognize different key residues locating on the gp42 N-domain. Among the nine mAbs, 4H7, 4H8 and 11G10 cross-react with rhLCV-gp42 while other mAbs specifically recognize EBV-gp42. Our newly obtained mAbs provide a useful tool for investigating the gp42 function and viral infection mechanism of γ-Herpesvirus. Furthermore, we assess the immunogenicity of the gp42 N-terminal region using the HBc149 particle as a carrier protein. The chimeric VLPs can induce high antibody titers and elicit neutralizing humoral responses to block EBV infection. More rational and effective designs are required to promote the gp42-N terminal region to become an epitope-based vaccine.